A novel Cs2NbOF5:Mn4+ oxyfluoride red phosphor for light-emitting diode devices. Issue 45 (12th September 2018) - Ming, Hong; Zhang, Junfei; Liu, Lili; Peng, Jiaqing; Du, Fu; Ye, Xinyu; Yang, Youming; Nie, Huaping
Abstract : A brand-new Mn 4+ -activated Cs2 NbOF5 oxyfluoride phosphor was developed for light-emitting diode devices. Abstract : The addition of a red-emitting phosphor to YAG:Ce 3+ -based white light-emitting diodes (WLEDs) greatly facilitates their applications in the field of high-color-rendering-index warm solid-state lighting. It is highly desirable to develop a red phosphor with satisfactory spectral features and low synthesis cost. In this study, a novel non-rare-earth and nonequivalent doping type of Cs2 NbOF5 :Mn 4+ oxyfluoride red-emitting phosphor with high luminous efficiency was obtained via a facile room-temperature co-precipitation method, and its morphology and luminescent properties were investigated in detail. The Cs2 NbOF5 :Mn 4+ phosphor with micro-rod-like morphology exhibited broad band absorption at blue light region (∼474 nm) and narrow bandwidth emissions at red region (∼633 nm). The color purity of the Cs2 NbOF5 :Mn 4+ phosphor was calculated to be about 99%, and the internal quantum yield (QY) under 474 nm excitation was 63.4%. The concentration quenching of Mn 4+ in Cs2 NbOF5 matrix was mainly due to dipole–dipole interactions, and the activation energy of temperature quenching was calculated to be ∼0.2610 eV. The demonstration of a blue InGaN LED chip in combination with a blend of newly developed Cs2 NbOF5 :Mn 4+ red phosphor and YAG:Ce 3+ yellow phosphor greatly decreased the correlated color temperature (CCT) from 6255 to 3517 K while significantly improving the color rendering index (CRI) from 72.5 to 87.5. It deserves to be mentioned that the brand-new matrix to phosphor in the present study can be extended to various niobium/tantalum oxyfluoride series, which is very helpful for developing and designing new red phosphors.